2020
DOI: 10.3389/fpsyg.2020.01417
|View full text |Cite
|
Sign up to set email alerts
|

“Does My Teacher Believe I Can Improve?”: The Role of Meta-Lay Theories in ESL Learners’ Mindsets and Need Satisfaction

Abstract: Supporting students’ growth mindsets (i.e., beliefs that ability can be improved) and basic psychological needs (i.e., needs for autonomy, competence, and relatedness) is an important way to sustain their motivation and resilience after challenging situations. We argue that others’ feedback may support or undermine mindsets and need satisfaction simultaneously through students’ meta-lay theories—that is, students’ perceptions of whether others (in this case, their teacher) believe that ability can be improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 66 publications
(132 reference statements)
0
29
0
1
Order By: Relevance
“…Moreover, we found that the relation between growth language mindsets and low anxiety was not due to high self‐esteem—growth language mindsets and self‐esteem are independently linked to lower anxiety. To help linguistic minority students break this vicious cycle of language anxiety, educators can encourage them to internalize growth language mindsets (see Lou & Noels, 2020a). Although there are existing workshops and intervention programs that expose students to growth language mindsets about intelligence (e.g., Paunesku et al., 2015), these programs could benefit migrant university students more if they were tailored to the language and intercultural communication context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we found that the relation between growth language mindsets and low anxiety was not due to high self‐esteem—growth language mindsets and self‐esteem are independently linked to lower anxiety. To help linguistic minority students break this vicious cycle of language anxiety, educators can encourage them to internalize growth language mindsets (see Lou & Noels, 2020a). Although there are existing workshops and intervention programs that expose students to growth language mindsets about intelligence (e.g., Paunesku et al., 2015), these programs could benefit migrant university students more if they were tailored to the language and intercultural communication context.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that language mindsets are also important for language development and psychological adaptation outside of the classroom (Lou & Noels, 2019b). Specifically, migrants who strongly endorsed fixed mindsets felt more anxious about using English with English speakers because they focused on their ‘performance’ and did not want to be seen as lacking competence, and so, they were less likely to seek opportunities to improve English or more likely to avoid using English (Lou & Noels, 2020a). Consequently, migrants with strong fixed mindsets might be less likely to develop English proficiency.…”
Section: Language Mindsets and Adaptive Outcomesmentioning
confidence: 99%
“…Generally, the literature confirms that teacher feedback can effectively influence student motivation (e.g., Pereira et al, 2016;Van der Kleij, 2019;Lou and Noels, 2020). Scaffolding feedback may be the most positive type, as it was shown to influence student learning by facilitating the promotion of student independent learning .…”
Section: Relationships Between Teacher Feedback and Student Motivationmentioning
confidence: 97%
“…Moreover, studies suggested that teachers' sincere and specific praise can reinforce students' desired learning behaviors and significantly increase their extrinsic motivation and self-efficacy (Haimovitz and Corpus, 2011;. Contrastingly, teacher feedback can also be ineffective or even detrimental for student motivation (Lou and Noels, 2020). A study showed that verification feedback can exert negative effects on students' motivation because they tend to redirect students' focus from addressing problems to competing with peers, or please the teacher or their parents (Lipnevich and Smith, 2008).…”
Section: Relationships Between Teacher Feedback and Student Motivationmentioning
confidence: 99%
“…For example, research suggests that teachers with fixed mindsets are more likely to provide consolation-oriented support to students whom they have judged as having low potential based even on a single mediocre test performance (e.g., reassuring them that 'not everyone has math talent', trying to reduce pressure by calling on them less in class or assigning them less homework) rather than constructive support oriented toward improvement [75]. Unfortunately, this consolation behavior conveys to students that they have low hope for growth, reducing their engagement and motivation [75,76]. Thus, teachers' expectations of students and ability beliefs may interact to heighten disparate interaction and resulting disparities in achievement, particularly if teachers have lower expectations for some groups of students than others.…”
Section: Disparate Interactionmentioning
confidence: 99%